2009
DOI: 10.1007/s00066-009-2020-x
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Beam Therapy for Hepatocellular Carcinoma Associated with Portal Vein Tumor Thrombosis*

Abstract: PBT improved local control and significantly prolonged survival in HCC patients with PVTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 39 publications
2
79
0
Order By: Relevance
“…A series of 35 patients with HCC portal venous thrombosis received treatment of 50 to 72 CGE which resulted in local control rates of over 45% at 2 years. Only 3 of these patients developed severe acute toxicity (36). The excellent conformality of proton beams may open up the possibilities for retreatment in the case of HCC progression or for synchronous tumors arising elsewhere in the liver.…”
Section: Clinical Outcomes Of Hcc Treated With Proton Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…A series of 35 patients with HCC portal venous thrombosis received treatment of 50 to 72 CGE which resulted in local control rates of over 45% at 2 years. Only 3 of these patients developed severe acute toxicity (36). The excellent conformality of proton beams may open up the possibilities for retreatment in the case of HCC progression or for synchronous tumors arising elsewhere in the liver.…”
Section: Clinical Outcomes Of Hcc Treated With Proton Radiotherapymentioning
confidence: 99%
“…One of the larger prospective studies was a phase II trial examining outcomes of proton radiotherapy in HCC patients with cirrhosis demonstrated a 66% 2-year overall survival rate after delivering 76 CGE in 3.8 CGE daily fractions (36). Loma Linda University reported results of the largest prospective phase II trial describing the use of proton radiotherapy in patients with HCC.…”
Section: Clinical Outcomes Of Hcc Treated With Proton Radiotherapymentioning
confidence: 99%
“…Local control rates upto 45% for 2 years have been reported. 22 Similarly encouraging responses with retreatment for recurrent or synchronous HCC have been reported with 5-year local control rate of 87.8% and 5-year overall survival rate of 56%. 23 A prospective phase II trial had reported preliminary results in 34 cases of unresectable HCC with 2-year local control of 75% and overall survival of 55% and no incidence of RILD.…”
Section: Charged Particle Therapymentioning
confidence: 68%
“…Along with these two high-volume studies, the group has also extensively published subgroup analyses on HCC associated with severe cirrhosis (42,43), severe ascites (30), portal vein tumor thrombosis (44,45), porta hepatis involvement (46), limited treatment options (47), elderly patients (48), LR (29,36), tumor adjacent to the GI tract (49), large-sized tumors (50), and altered fractionation (51,52).…”
Section: Livermentioning
confidence: 99%